Standardization Of Pinyaram Recipes In Titian Panjang Kanagarian Kayutanam Padang Pariaman District - Handayani, Utari; Gusnita, Wiwik (Universitas Negeri Padang, 2023)
This research was motivated by differences in the materials and tools used, the manufacturing process, and the quality of pinyaram in Titian Panjang Kanagarian Kayutanam, Padang Pariaman District. This study aims to standardize pinyaram recipes at Titian Panjang Kanagarian Kayutanam, Padang Pariaman District which includes materials and tools, manufacturing techniques and analyzes the quality of pinyaram so as to produce a good recipe. This type of research is a qualitative and quantitative research using a mixed method. Qualitative data sources were obtained from research informants and quantitative data sources were obtained from trained panelists and limited panelists. Qualitative data collection techniques are observation, interviews, documentation, and quantitative data collection techniques are organoleptic test questionnaire format. The qualitative data analysis techniques are: data reduction, data presentation, drawing conclusions, and quantitative data analysis techniques using the formula (Mx=∑ x / N ) and testing the validity of qualitative data. Based on the research results obtained 10 Pinyaram recipes in Titian Panjang Kanagarian Kayutanam. The pinyaram recipe was analyzed and tested with 5 selected recipes. The results of the organoleptic test obtained the highest value by Mrs. Nita and used as a standardization of the converted pinyaram recipe. The standardization of the pinyaram recipe was carried out by organoleptic tests to get good quality pinyaram including: shape (round), color (golden yellow), aroma (fragrant), texture (soft) and taste (sweet).